Discrimination training in the treatment of pica and food scavenging - Johnson, C R; Hunt, F M; Siebert, M J (Behavior modification, 1994)
Pica and scavenging are serious, sometimes life-threatening behavior problems among a significant percentage of individuals with mental retardation. This study describes procedures developed to reduce life-threatening pica and food scavenging in two adolescents with severe to profound mental retardation. Treatment was designed to teach the subjects to discriminate safe from unsafe items by training them to ingest only those items put on a specified placemat and to communicate with simple signs or gestures to obtain more food to be put on the mat. Discrimination was achieved by praising subjects when they selected and ingested items from their placemats and delivering a mild punisher when attempts to ingest nonplacemat items were made. A multiple baseline design across settings was used to evaluate the effects of the treatment package in three inpatient settings. All environments were "baited" with both edible and inedible items. Our treatment procedures appeared to be effective in reducing pica in each of the settings. Generalization of treatment effects to natural environments for one of the two subjects was documented.